“I Was Too Chickenhearted to Publish it”: Seán O’Faoláin, Displacement and History Re-Written - John Grant (Estudios Irlandeses, 2017)
This article concerns the re-writing of an Irish historical moment within the short story genre, focusing on the renowned Irish writer Seán O’Faoláin (1900-1991). O’Faoláin, it is argued here, attempted to alleviate the “trauma” of the Irish Civil War (1922-1923) through his writing. This piece offers a comparative analysis of O’Faoláin’s treatment of the Civil War in his autobiography, Vive Moi! (1993), and in two short stories, “Fugue” and “The Bomb Shop”, from the collection Midsummer Night Madness (1932), examining his re-writing of several key episodes from the Civil War. As this article demonstrates, O’Faoláin re-wrote these so that they became part of a less contentious War of Independence narrative.